2010
DOI: 10.1371/journal.pgen.1001247
|View full text |Cite|
|
Sign up to set email alerts
|

A Quantitative Systems Approach Reveals Dynamic Control of tRNA Modifications during Cellular Stress

Abstract: Decades of study have revealed more than 100 ribonucleoside structures incorporated as post-transcriptional modifications mainly in tRNA and rRNA, yet the larger functional dynamics of this conserved system are unclear. To this end, we developed a highly precise mass spectrometric method to quantify tRNA modifications in Saccharomyces cerevisiae. Our approach revealed several novel biosynthetic pathways for RNA modifications and led to the discovery of signature changes in the spectrum of tRNA modifications in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
537
3
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 407 publications
(562 citation statements)
references
References 46 publications
18
537
3
4
Order By: Relevance
“…[26][27][28]32 Recently it was suggested that levels of certain modified nucleosides in tRNA, among them ncm 5 U, mcm 5 U and mcm 5 s 2 U could be altered in response to various stress conditions. 67 However, the levels of the ncm 5 U, mcm 5 U and mcm 5 s 2 U nucleosides were not quantified in individual tRNA isoacceptors rather they were quantified in bulk tRNA. Therefore, it is not possible to distinguish between regulation of modification on individual tRNA isoacceptors or if the levels of the tRNA isoacceptors are altered.…”
mentioning
confidence: 99%
“…[26][27][28]32 Recently it was suggested that levels of certain modified nucleosides in tRNA, among them ncm 5 U, mcm 5 U and mcm 5 s 2 U could be altered in response to various stress conditions. 67 However, the levels of the ncm 5 U, mcm 5 U and mcm 5 s 2 U nucleosides were not quantified in individual tRNA isoacceptors rather they were quantified in bulk tRNA. Therefore, it is not possible to distinguish between regulation of modification on individual tRNA isoacceptors or if the levels of the tRNA isoacceptors are altered.…”
mentioning
confidence: 99%
“…The paradigmatic example was the work of Dedon and coworkers, who studied the changes in modified nucleoside abundance for yeast as the organism was subjected to different stress conditions. 21 In this study, a single labeled deoxyadenosine standard was mixed with the sample to allow the authors to normalize the signal response from analysis to analysis and from sample to sample. They then found statistically significant differences in the signal response for 23 modifications between untreated and treated yeast cells.…”
Section: Modification Network -Quantifying Changes In Modified Nuclementioning
confidence: 99%
“…In accordance with these finding, knock out mutants of trm4 (catalyzes m 5 C) and trm7 (catalyzes Cm) were found to be less viable after hydrogen peroxide exposure as compared to wild type yeast. 21 The capability to routinely monitor dynamic changes in RNA modification levels 22 enabled Dedon and Begley to propose a regulatory model that correlates such changes with the transcriptional and translational needs of an organism. 23 While an internal standard can provide a means to compare 2 samples, a more accurate determination of the quantity of www.landesbioscience.comindividual nucleosides can be obtained by using an isotope dilution method.…”
Section: Modification Network -Quantifying Changes In Modified Nuclementioning
confidence: 99%
“…These have allowed a greater parity of the occurrence and fluidity of this epigenetic modification [30]. There is growing evidence that these RNA modifications can respond rapidly to a variety of stimuli, particularly stress [31,32]. Recently, FTO has been further implicated in the complicated control of RNA epigenetics by evidence which suggests it may catalyse further reactions oxidising the N(6)-methyladenosine to form the intermediate product N(6)-hydroxymethyladenosine, which is followed by the formation of the further oxidised product N(6)-formyladenosine [33].…”
Section: Renewed Interest In Rna Epigeneticsmentioning
confidence: 99%